The power to change the world - Romoleroux, Antonio (2020)
Some time ago, the young Romoleroux, a prodigious artist—one of those whom the renowned art critic Arthur Danto says are no longer being forged—and who, at the age of 27, had already won the Mariano Aguilera First Prize for Painting; and with multiple awards already under his belt at his young age, he felt a devastating need to seek new directions once success had consolidated him in his most admired formats, such as those in the series Mi esencia en tus sentidos (My essence in your senses), which preceded the award and consolidated him as a renowned artist.